Non-targeted metabolomics and network pharmacology of Taohong Siwu Decoction in hepatic fibrosis mouse model using high resolution mass spectrometry - Li, Shengsheng; Qi, Shenglan; Li, Rongsheng; Yang, Fangming; Niu, Zhenyi; Liu, Wei; Ma, Suping; Xiao, Zhun (Frontiers in Molecular Biosciences, 2025)
IntroductionTaohong Siwu Decoction (THSW Decoction), a classic formula for treating blood stasis, has demonstrated significant clinical efficacy in the treatment of hepatic fibrosis. However, its primary active components and mechanisms of action remain unclear.MethodsIn this study, a carbon tetrachloride (CCl4)-induced hepatic fibrosis mouse model was established to evaluate THSW Decoction’s therapeutic effects. Ultra-high performance liquid chromatography-quadrupole/Orbitrap high-resolution mass spectrometry (UHPLC-Q-Exactive Orbitrap HRMS) was employed to identify the main prototype chemical components of THSW Decoction in the blood, while non-targeted metabolomics analysis was performed using a Waters Synapt G2-Si QTOF mass spectrometer (Synapt G2-Si QTOF HRMS system). Network pharmacology and metabolomic data were integrated to elucidate the therapeutic targets, differential metabolites, and signaling pathways of THSW Decoction. Molecular docking and binding affinity predictions between key targets and principal compounds were performed using PyMOL software. Furthermore, molecular dynamics simulations were conducted to evaluate the structural stability and binding interactions. Finally, core targets were validated in vivo.ResultsTHSW Decoction effectively reduced CCl4-induced serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, alleviating liver inflammation and collagen deposition. Forty-five blood components were detected, with 616 corresponding drug targets identified, including 419 overlapping targets for anti-hepatic fibrosis. The core protein-protein interaction (PPI) network comprised 59 nodes and 570 edges. Enrichment analysis revealed that THSW Decoction’s blood components primarily modulated biological processes such as positive regulation of response to external stimuli and oxygen content. Key signaling pathways included PI3K-Akt, estrogen, relaxin, and MAPK. Non-targeted metabolomics identified 148 differential metabolites between the model and normal groups, and 156 between the THSW Decoction and model groups. Thirty-five overlapping metabolites were enriched in cAMP, phospholipase D, and GnRH signaling pathways. Twenty intersection targets linked blood components, metabolites, and hepatic fibrosis. PPI analysis ranked JUN, PTGS2, BCL2, ESR1, and PPARG as the top five targets. A “drug-component-target-metabolite” network highlighted ferulic acid, p-hydroxycinnamic acid, 3-hydroxy-4-methoxycinnamic acid, ferulaldehyde, and vanillic acid as the top five blood components. Molecular docking and molecular dynamics simulations revealed that 3-hydroxy-4-methoxycinnamic acid binds stably to the core target PPARG, exhibiting a binding free energy of −93.68 kJ/mol. In vivo validation showed that THSW Decoction upregulated JUN and downregulated ESR1 expression in the liver.DiscussionThis study elucidates THSW Decoction’s key blood components, potential targets, and mechanisms in the treatment of hepatic fibrosis, providing a foundation for further research.